Concomitant reduction of c-Myc expression and PI3K/AKT/mTOR signaling by quercetin induces a strong cytotoxic effect against Burkitt's lymphoma. (October 2016) - Granato, Marisa; Rizzello, Celeste; Romeo, Maria Anele; Yadav, Shivangi; Santarelli, Roberta; D'Orazi, Gabriella; Faggioni, Alberto; Cirone, Mara
Abstract: Burkitt's lymphoma is an aggressive B cell lymphoma whose pathogenesis involves mainly c-Myc translocation and hyperexpression, in addition to antigen-independent BCR signaling and, in some cases, EBV infection. As result of BCR signaling activation, the PI3K/AKT/mTOR pathway results constitutively activated also in the absence of EBV, promoting cell survival and counterbalancing the pro-apoptotic function that c-Myc may also exert. In this study we found that quercetin, a bioflavonoid widely distributed in plant kingdom, reduced c-Myc expression and inhibited the PI3K/AKT/mTOR activity in BL, leading to an apoptotic cell death. We observed a higher cytotoxic effect against the EBV-negative BL cells in comparison with the positive ones, suggesting that this oncogenic gammaherpesvirus confers an additional resistance to the quercetin treatment. Besides cell survival, PI3K/AKT/mTOR pathway also regulates autophagy: we found that quercetin induced a complete autophagic flux in BL cells, that contributes to c-Myc reduction in some of these cells. Indeed, autophagy inhibition by chloroquine partially restored c-Myc expression in EBV-positive (Akata) and EBV-negative (2A8) cells that harbor c-Myc mutation. Interestingly, chloroquine did not affect the quercetin-mediated reduction of c-Myc expression in Ramos cells, that have no c-Myc mutation in the coding region, although autophagy was induced. These results suggest that mutant c-Myc could be partially degraded through autophagy in BL cells, as previously reported for other mutant oncogenic proteins.